A delayed benign anastomotic stricture after anterior resection for sigmoid adenocarcinoma with concomitant collagenous colitis. Issue 3 (7th March 2023) - Wallace, Lauren; Gallagher, James
Abstract: Benign anastomotic strictures most commonly occur within 3–12 months after anterior resection (AR) with chronic symptoms amenable to endoscopic treatment. This case describes an acute large bowel obstruction secondary to a severe delayed benign anastomotic stricture in a 74-year-old female who had previously underwent a laparoscopic AR for sigmoid adenocarcinoma 3 years prior. The pathophysiology of benign anastomotic strictures remains poorly understood. This case was likely multifactorial. Potential contributing factors include anastomotic ischaemia and concomitant collagenous colitis, with inflammation leading to fibrosis and stricture development. Surgical techniques to optimize anastomotic vascularity are important to consider, particularly in older patients with multiple co-morbidities.